Discourse change in a changing society: a critical discourse analysis of political advertisement in Jordan before and after the Arab Spring - Al-Momani, Kawakib (Círculo de Lingüística Aplicada a la Comunicación, 2016)
This study provides a critical discourse analysis of election advertisements in Jordanian society before and after the political uprisings in the Arab world, referred to as the “Arabic Spring”, which started in 2011. It is argued here that these events have left traces on political advertisement. This study aims to uncover the shifts in discourse that have occurred in election advertisements since 2011. To this end, a sum of 150 advertisements from three election campaigns 2007, 2010 and 2013 was collected from different media sources during the campaigns of those elections. The data were analyzed both qualitatively and quantitatively. The analysis showed that the advertisements of 2013 elections manifested different strategies, addressing mostly sociopolitical issues, compared to the other two elections which showed little political concern and focused on socio-economic issues. It is hoped that this study will contribute to cross cultural understanding, multimodality and critical discourse analysis.